2011
DOI: 10.4065/mcp.2011.0415
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Delayed Microbiology Results After Hospital Discharge: Improving Patient Safety Through an Automated Medical Informatics Tool

Abstract: ). © 2011 Mayo Foundation for Medical Education and ResearchC ultures for bacteria, fungi, viruses, and mycobacteria require days to weeks to produce positive results. For many hospitalized patients, culture results are not available at the time of dismissal. In fact, approximately 41% of patients discharged from the hospital have pending laboratory test results, 1,2 and the most common results requiring urgent action come from pending microbiology tests. Results of a delayed positive culture commonly require … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…1 Wilson et al described a notification system targeting infectious disease specialists with post-discharge non-urine microbiology results, but did not evaluate the impact of the system with a concurrent control group. 4 Dalal et al found that hospital-based clinicians recognized the importance of proper test result management, but failed to adopt an electronic test result management 12 To improve adoption, we strove to maximize the likelihood that our alerts represented true untreated infections. In addition, we attempted to aggregate useful information in the alert to enhance the efficiency of result follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Wilson et al described a notification system targeting infectious disease specialists with post-discharge non-urine microbiology results, but did not evaluate the impact of the system with a concurrent control group. 4 Dalal et al found that hospital-based clinicians recognized the importance of proper test result management, but failed to adopt an electronic test result management 12 To improve adoption, we strove to maximize the likelihood that our alerts represented true untreated infections. In addition, we attempted to aggregate useful information in the alert to enhance the efficiency of result follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Failure to follow up on these results in a timely fashion can delay the diagnosis and treatment of infections, leading to patient harm and risk of litigation. 5,6 The proper communication of test results that are pending at hospital discharge is becoming more crucial as hospitalized patients are increasingly cared for by hospital-based clinicians rather than their primary care providers (PCPs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Timely, accurate patient sample results are essential in order for this to occur. Traditional microbiology, however, is often culture-based and reportable results can sometimes take days to deliver [2]. Additionally there is a sustainability challenge in microbiology services due to reduced staffing, increasing costs, greater demand for services and a rising ageing population [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Another option is to use a more hands-on approach in which software flags a chart for review by an infectious disease physician when a result of interest is reported after discharge. Once the infectious disease specialist has reviewed the result and the patient chart, the specialist can subsequently contact the treating physician if a change in therapy is potentially indicated (40).…”
Section: Postdischarge Resultsmentioning
confidence: 99%